Atividade inseticida de extratos de plantas no controle de formiga cortadeira, em cafeeiro - Torres, Andrea de Fátima; Lasmar, Olinto [UNESP]; Andrade Carvalho, Geraldo; Costa Santa-Cecília, Lenira Viana; Zanetti, Ronald; de Oliveira, Denilson (My University, 2013)
The objective of this work was to evaluate the efficiency of extracts of plants from Minas Gerais in the control of leaf cutting ant Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae). Seventy plant extracts were evaluated, being applied to the diet of the test insects. It was verified that only the botanical extracts Eugenia florida and Eugenia handroana (Myrtaceae), Trichilia pallida (Meliaceae) and Zanthoxylum pohlianum (Rutaceae) present lethal effect, with mortality average of 16.7; 23.3; 19.7 and 17.3%, respectively.
Insecticidal activity of extracts of plants in the control of leaf cutting ant in coffee
Keywords: Atta spp.; Coffea arabica; Mortality; Natural products